A study on wild edible plants for human consumption in Hizan county of Bitlis, Turkey (Bangladesh Journal of Plant Taxonomy, 2020)
This study covers the edible plants in Hizan where there is a rich culture of plant consumption. The study was conducted between 2018 and 2019 to record the culture of traditional food plant use of the local people in Hizan. In this regard, the face-to-face interviews with the local people were made, and the relevant plants used were collected and identified. A total of 65 species of wild edible plants belonging to 24 families were identified, and their different traditional usages were categorized as cooked, cheese making, rennet, specie and gum producing, and as raw or beverages etc. In addition, the use-value (VU) index was calculated for each species. The mostly used species included Rheum ribes L. (UV: 0.70), Gundelia tournefortii L. (0.66), Silene vulgaris (Moench) Garcke, Rosa canina L. (0.64), Urtica dioica L. (0.63), Malva neglecta Wallr. (0.61), and Pistacia khinjuk Stocks (0.60). The culture of edible plant use is widespread throughout the Anatolia. However, traditional uses of many wild plants have not been recorded yet. Therefore, this research will be an important contribution to the preservation of the cultural heritage associated with traditional wild edible plants in this region.Bangladesh J. Plant Taxon. 27(2): 377-389, 2020 (December)